PSYCHOLOGICAL THEORY AND METHODOLOGY OF THE STUDY OF PERSONALITY IN OSVITOLOGIYA - Pobirchenko, Neonila; Serhieienkova Оksana (Continuing Professional Education: Theory and Practice, 2019)
In the article the factor of personality is reflected in educational space. Theoretical ideas and methodological going are reasonable near rich in content determination of factor of personality in innovative industry – educology (“osvitolohiia”). The purpose of the article is to disclose the factor of the personality as the priority regularity of the development of the new scientific approach in the integrated research of the osvitological principles. It was used the methods of theoretical, methodological analysis of the scientific sources and experience of the practical implementation of the main learning outcomes. Summarizing the study of the key notion “personality factor” it is advisable to emphasize the actuality of its development and implementation in the multidisciplinary educational process of the research of the new field. Accordingly, the results of the research of the nature and objects of the new scientific field – osvitolohiya – can make innovation area of the personal development in terms of multidisciplinary education of the modern university. This osvitological space is the synergistic for its meaning, incentive and subjective for its influences that are directed to the formation of students’ competitiveness as necessary quality of the specialist in market education. It is provided for making changes in the organization of the training activities. These changes relate to cognitive methods, scientific, organizational and other activities. “Osvitolohizm” as the integrated for its actions method of the establishing of the interdisciplinary connections in organizational improvement of the area.